Formulación y evaluación para la creación de una sucursal de la empresa CIVAL Ltda. en la zona norte de Colombia (2023)
In this project, the commercial, technical and financial viability of the creation of a branch of the company CIVAL Ltda. is determined, in order to enter the concrete plant maintenance market in the northern area of ​​Colombia, which includes the departments of Atlántico. , Magdalena, Bolívar, Cesar and Guajira. Using industrial engineering tools, a market investigation is carried out which results in the identification of a market with an unsatisfied demand that has not been served correctly by companies located in other sectors, generating that the attention is not given at the time it is required. This is seen as an opportunity to enter the market, installing a branch in the Barranquilla area because it is a midpoint in distance and time between the plants in the northern sector. In addition, demand and sales prices are projected to determine technical feasibility. To launch the branch, each of the services that will be offered to the market is described, in order to identify all the necessary human and material resources. Taking into account the projected demand and frequency, the time for service and availability of personnel, each of the resources is adjusted to take the next step to the micro location where the physical structure for the operation of the branch is designed and proposed in a 213 meter warehouse in the city of Barranquilla. Continuing with the financial study, all costs and expenses that may affect the operation of the branch are taken into account, creating an amortization and depreciation plan to project cash flows for 10 years, determining that the project is not financially viable. through indicators such as IRR, PAYBACK, among others.